(untitled) (Global Journal of Management and Business Research, 2018)
The present research aims to explain how sustainable involvement can influence the behavior of Algerian families for the purchase of a new car. The main hypothesis of this study was tested on a sample of 210 families. The data obtained were analyzed using structural equation models. The principal results that emerged from this investigation show that the identification of the cognitive and/or emotional purchase process, adopted by family members, could be a relevant avenue for companies to develop and enhance their products. The findings obtained could offer an opportunity to create strong and durable brands.